Polymorphisms in Long Noncoding RNA H19 Contribute to the Protective Effects of Coal Workers’ Pneumoconiosis in a Chinese Population - Wu, Qiuyun (Int J Environ Res Public Health, 2016)
The H19 is a kind of long noncoding RNA, which has been implicated in multiple biological functions. However, the associations between genetic variants in H19 and susceptibility of coal workers’ pneumoconiosis (CWP) have been seldom reported. In the present study, three potential polymorphisms (rs2067051, rs217727, and rs2839702) in H19 were genotyped in a case-control study including 703 CWP cases and 705 controls. We found that individuals with the H19 rs2067051 CT/TT genotypes showed a decreased risk of CWP compared with those with the CC genotype (adjusted OR = 0.64, 95%CI = 0.49–0.83, p = 0.001). Further stratified analyses revealed that the associations between variant genotypes of rs2067051 and the risk of CWP were more prominent in subjects of non-smokers (adjusted OR = 0.55, 95%CI = 0.39–0.79, p = 0.001) and CWP patients with Stage I (adjusted OR = 0.63, 95%CI = 0.46–0.86, p = 0.004). Additionally, the protective effects of H19 rs2067051 were also evident in coal miners both with dust exposure years <25 years (adjusted OR = 0.63, 95%CI = 0.42–0.95, p = 0.026) and ≥25 years (adjusted OR = 0.57, 95%CI = 0.40–0.80, p = 0.001). Our results indicated that rs2067051 in the H19 gene is correlated with a deceased risk of CWP in a Chinese population, which may be a potential genetic marker for prevention and intervention of CWP. Further functional studies are warranted to validate our findings.